The Correlation Between Coping Strategy and Stress of Parents Who Have Children with Autism - Windi Dwirexsi; Mamat Lukman; Imas Rafiyah (Journal of Nursing Care, 2018)
Autism was a very complex neurobiological developmental disorder. Parents with autistic children have a higher stress level than parents who have normal children, so use the effective coping strategy for parents who had an autistic child would make them prevented the excessive stress. Aim of the research was to find out relation of coping strategy and parents’ stress who had an autistic children. The research design was correlational design with a cross-sectional approach. Data collection used a questionnaire of the Coping Health Inventory for Parents and Parental Stress Scale. Result of study showed that coping strategy and parents’ stress who had an autistic child were mostly at range of medium coping strategy (57.7%) and moderate stress (76.9%). Result of Spearman’s Rank correlation test showed a negative relation between coping strategy and parents’ stress (r=0.699; p=0.000). There was a correlation between coping strategy and parents’ stress who had an autistic child in this research, which meant the better coping strategy the lower parents’ stress who had an autistic child. Based on these results, autistic agencies should be better able pay attention to improve ability of parents’ coping strategy who had autistic children.